Nanoparticle-Enhanced Acoustic Wave Biosensor Detection of Pseudomonas aeruginosa in Food - Sandro Spagnolo; Katharina Davoudian; Brian De La Franier; Robert Kocsis; Tibor Hianik; Michael Thompson (Biosensors)
A biosensor was designed for detecting Pseudomonas aeruginosa (P. aeruginosa) bacteria in whole milk samples. The sensing layer involved the antifouling linking molecule 3-(2-mercaptoethanoxy)propanoic acid (HS-MEG-COOH), which was covalently linked to an aptamer for binding P. aeruginosa. The aptasensor uses the thickness shear mode (TSM) system for mass-sensitive acoustic sensing of the bacterium. High concentrations (105 CFU mL−1) of nonspecific bacteria, E. coli, S. aureus, and L. acidophilus, were tested with the aptasensor and caused negligible frequency shifts compared to P. aeruginosa. The aptasensor has high selectivity for P. aeruginosa, with an extrapolated limit of detection (LOD) of 86 CFU mL−1 in phosphate-buffered saline (PBS) and 157 CFU mL−1 in milk. To improve the sensitivity of the sensor, gold nanoparticles (AuNPs) were functionalized with the same aptamer for P. aeruginosa and flowed through the sensor following bacteria, reducing the extrapolated LOD to 68 CFU mL−1 in PBS and 46 CFU mL−1 in milk. The frequency variations in the aptasensor are proportional to various concentrations of P. aeruginosa (102–105 CFU mL−1) with and without AuNPs, respectively. The low and rapid mass-sensitive detection demonstrates the ability of the aptasensor to quantitatively identify bacterial contamination in buffer and milk.